New species and records of Menoscelis Mulsant (Coleoptera: Coccinellidae) from French Guiana - Santos, Paula B.; Churata-Salcedo, Julissa M.; Almeida, Lúcia M. (Zootaxa, 2016)
Three new species of Menoscelis Mulsant, 1850 from French Guiana are described: Menoscelis angeloi sp. nov. (Holotype male deposited in MNHN: Point de vue du Bélvédère de Saül, 09.IX.2011, SEAG col.), M. cordata sp. nov. (Holotype female deposited in MNHN: Réserve Naturelle des Nouragues—Saut Pararé 04º02’N, 52º41’W, 08.IX.2009, SEAG col.) and M. flava sp. nov. (Holotype female deposited in MNHN: Montagne des Chevaux 04º44’56”N, 02º26’28”W, 14.I.2012, SLAM, SEAG col.). The male of M. insignis Mulsant is described, and an identification key to the species of Menoscelis is included. New geographic distribution records, maps and a checklist of the species are also provided.